GENERATIVE ARTIFICIAL INTELLIGENCE: A COMPARATIVE ANALYSIS OF PLATFORMS FOR INTERIOR/ENVIRONMENTAL DESIGN (REMUNOM, 2025)
This study addresses the integration of Generative Artificial Intelligence (AI) into Interior/Environmental Design, acknowledging the tension between historically intuitive design competencies and the emerging automation of project processes. The objective was to analyze the role of Generative AI tools in project visualization, assessing their contributions and limitations. To this end, a Comparative Case Study was conducted between two platforms, Rendair AI and ArchiVinci, which were tested under the same input criteria (3D model and textual prompt). The evaluation focused on photorealism and the suitability of these tools within the designer’s workflow. The results show that Generative AI functions as a strategic resource capable of enhancing the designer’s analytical creativity. Both platforms demonstrated the ability to produce highly photorealistic visual representations. Rendair AI showed greater technical fidelity and detail accuracy, resembling professional interior photography, while ArchiVinci excelled in co-creation processes, enabling agile exploration of atmospheric alternatives. Its use improves visual communication and accelerates project development, establishing itself as a transformative vector in spatial representation processes.